2019
DOI: 10.1093/humupd/dmz028
|View full text |Cite
|
Sign up to set email alerts
|

Sperm recovery and ICSI outcomes in men with non-obstructive azoospermia: a systematic review and meta-analysis

Abstract: BACKGROUND Factor affecting sperm retrieval rate (SRR) or pregnancy rates (PR) after testicular sperm extraction (TESE) in patients with non-obstructive azoospermia (NOA) have not been systematically evaluated. In addition, although micro-TESE (mTESE) has been advocated as the gold standard for sperm retrieval in men with NOA, its superiority over conventional TESE (cTESE) remains conflicting. OBJECTIVE AND RATIONALE The obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
156
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(173 citation statements)
references
References 136 publications
13
156
3
1
Order By: Relevance
“…No difference was observed in p/cAZFcs in undamaged embryo count after PGT. This result was aligned with our series with no AZF deletion as well as other studies (Corona et al, 2019; Gnessi et al, 2018; Liu et al, 2017). There was no difference between pathological scores between p/cAZFcs.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…No difference was observed in p/cAZFcs in undamaged embryo count after PGT. This result was aligned with our series with no AZF deletion as well as other studies (Corona et al, 2019; Gnessi et al, 2018; Liu et al, 2017). There was no difference between pathological scores between p/cAZFcs.…”
Section: Discussionsupporting
confidence: 93%
“…While the fragmentation time in cAZFcs was ≥11 hr (≤ 5/hr normal), the fragmentation time in all AZFcs was 5 hr. The fact that AZFcs had no negative impact on embryo fragmentation was concordant with the other genetic disorders as well (Corona et al, 2019; Gnessi et al, 2018; Liu et al, 2017). No difference was observed in p/cAZFcs in undamaged embryo count after PGT.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…27 Lastly, the superiority of mTESE as compared to cTESE in NOA men has been extensively investigated in the previous literature but with conflicting results. 41 This is particularly true also in the Klinefelter population. Only few reports have shown that mTESE could be associated with better SRR than cTESE.…”
Section: Discussionmentioning
confidence: 92%
“…Sperm recovery and ICSI outcomes in men with non-obstructive azoospermia: a systematic review and meta-analysis. Corona G, Minhas S, Giwercman A [10].…”
Section: A Systematic Review and Meta-analysis Of Clinical Trials Impmentioning
confidence: 99%